Peran Manajemen Personalia Dalam Mendorong Perfoma Guru PAI di Sekolah Menengah Pertama - Neysa Salsabila Felasufa Amadea; Lintang Ahmad Mustika Aji; Kory Aznam Ashari; Muhammad Nurul Ikhsan; Krisna Rasyid Al Fittoh; Anaas Tri Ridlo Dina Yuliana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The quality of education in Indonesia is arguably still very low. This is very influential for the younger generation in the future, especially for educators, improving the quality of education is very important to do because there are many inhibiting factors to achieve the quality of education in Indonesia until now. This is in line with the research objective, which is to describe the teacher's role in supporting and improving the quality of education at SMP N 3 Godean. This research was conducted at SMP N 3 Godean. This research is a qualitative research using a descriptive approach. The research instrument used interviews. Respondents research vice principals and teachers BK. By using this approach, the author can describe the role of personnel management in improving teacher performance.